ANALISIS NILAI-NILAI PANCASILA DALAM KESENIAN MADIHIN MASYARAKAT SUKU BANJAR DI KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Yosi Novrinda; Zahirman '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is not only based on the reason that Madihin's performances which are full of advice, but also because of the issue of pantun-rhyme using the words that that have negative connotation, such as using language that is not polite, using words and sentences that impressed vulgar that should not be known by children. And Madihin performances are often held late into the night. Even sometimes in appearance madihin always start with incense burning with the aim of repel the spirits and to smoothly in delivery madihin. The formulation of the problem in this study is how the values of Pancasila which is contained in Madihin art Banjar tribe society in Batang Tuaka Sub-district Indragiri Hilir Regency. The purpose of this study is to analyze the values of Pancasila contained in the art Madihin Banjar tribe community in Batang Tuaka district Indragiri Hilir Regency. To determine the size of the sample quantity, the writer uses purposive sampling. Purposive sampling is a technique of taking or determining the sample with certain considerations. Based on this explanation, the authors take a sample of 30 people. Based on the result of the research, it can be concluded that the percentage of respondents' recapitulation of the answer of questionnaire about the analysis of Pancasila values in Madihin art tribe of Banjar people in Batang Tuaka district of Indragiri Hilir is different. There are 59.2% who answer “Yes” and 40. 8% who answer “No”.Keywords: Pancasila Values, Madihin Art